Mapping the mosaic sequence of primate visual cortical development - Mundinano, Inaki-Carril; Kwan, William Chin; Bourne, James A. (Frontiers in Neuroanatomy, 2015)
Traditional ‘textbook’ theory suggests that the development and maturation of visual cortical areas occur as a wave from V1. However, more recent evidence would suggest that this is not the case, and the emergence of extrastriate areas occurs in a non-hierarchical fashion. This proposition comes from both physiological and anatomical studies but the actual developmental sequence of extrastriate areas remains unknown. In the current study, we examined the development and maturation of the visual cortex of the marmoset monkey, a New World simian, from embryonic day 130 (15 days prior to birth) through to adulthood. Utilizing the well-described expression characteristics of the calcium-binding proteins calbindin and parvalbumin, and nonphosphorylated neurofilament for the pyramidal neurons, we were able to accurately map the sequence of development and maturation of the visual cortex. To this end, we demonstrated that both V1 and middle temporal area (MT) emerge first and that MT likely supports dorsal stream development while V1 supports ventral stream development. Furthermore, the emergence of the dorsal stream-associated areas was significantly earlier than ventral stream areas. The difference in the temporal development of the visual streams is likely driven by a teleological requirement for specific visual behavior in early life.